Serum uric acid to high-density lipoprotein cholesterol ratio predicts all-cause mortality in adults with metabolic dysfunction associated steatotic liver disease - Yingyong Ou; Zihan Qin; Pinze Wang; Fan Zou (Scientific Reports)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is one of the most prevalent chronic metabolic diseases worldwide. While serum uric acid (SUA) and high-density lipoprotein cholesterol (HDL) are individually associated with the development of MASLD, the prognostic effect of the UA, HDL and SUA-to-HDL ratio (UHR) on the all-cause mortality of MASLD patients remains unexplored. This study utilized data from 4280 MASLD patients in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. UHR was calculated by dividing SUA by HDL, and its association with all-cause mortality was assessed using Cox proportional hazards models. Adjustments were made for demographic, lifestyle, and clinical factors. A one-standard-deviation increase in UA or UHR was associated with a 19% (HR 1.19, 95% CI 1.08–1.31, P < 0.001) or 18% (HR 1.18; 95% CI 1.07–1.30; P < 0.001) higher risk of all-cause mortality of MASLD participants respectively, while no association was found between HDL and mortality. SUA and UHR are promising predictors of all-cause mortality in MASLD patients, offering clinicians a valuable biomarker for related risk stratification. Its inclusion in clinical assessments could guide interventions and improve prognosis, advancing management for MASLD patients.